DWI-ASPECTS (Diffusion-Weighted Imaging–Alberta Stroke Program Early Computed Tomography Scores) and DWI-FLAIR (Diffusion-Weighted Imaging–Fluid Attenuated Inversion Recovery) Mismatch in Thrombectomy Candidates: An Intrarater and Interrater Agreement Study. Issue 1 (January 2018) - Fahed, Robert; Lecler, Augustin; Sabben, Candice; Khoury, Naim; Ducroux, Célina; Chalumeau, Vanessa; Botta, Daniele; Kalsoum, Erwah; Boisseau, William; Duron, Loïc; Cabral, Dominique; Koskas, Patricia; et al.
Abstract : Background and Purpose—: We aimed to study the intrarater and interrater agreement of clinicians attributing DWI-ASPECTS (Diffusion-Weighted Imaging–Alberta Stroke Program Early Computed Tomography Scores) and DWI-FLAIR (Diffusion-Weighted Imaging–Fluid Attenuated Inversion Recovery) mismatch in patients with acute ischemic stroke referred for mechanical thrombectomy. Methods—: Eighteen raters independently scored anonymized magnetic resonance imaging scans of 30 participants from a multicentre thrombectomy trial, in 2 different reading sessions. Agreement was measured using Fleiss κ and Cohen κ statistics. Results—: Interrater agreement for DWI-ASPECTS was slight (κ=0.17 [0.14–0.21]). Four raters (22.2%) had a substantial (or higher) intrarater agreement. Dichotomization of the DWI-ASPECTS (0–5 versus 6–10 or 0–6 versus 7–10) increased the interrater agreement to a substantial level (κ=0.62 [0.48–0.75] and 0.68 [0.55–0.79], respectively) and more raters reached a substantial (or higher) intrarater agreement (17/18 raters [94.4%]). Interrater agreement for DWI-FLAIR mismatch was moderate (κ=0.43 [0.33–0.57]); 11 raters (61.1%) reached a substantial (or higher) intrarater agreement. Conclusions—: Agreement between clinicians assessing DWI-ASPECTS and DWI-FLAIR mismatch may not be sufficient to make repeatable clinical decisions in mechanical thrombectomy. The dichotomization of the DWI-ASPECTS (0–5 versus 0–6 or 0–6 versus 7–10) improved interrater and intrarater agreement, however, its relevance for patients selection for mechanical thrombectomy needs to be validated in a randomized trial. Abstract : Supplemental Digital Content is available in the text.